Moderasi Sosialisasi Perpajakan Atas Pengaruh Literasi Akuntansi dan Pemahaman PP Nomor 55 Tahun 2022 Terhadap Kepatuhan Wajib Pajak UMKM di E-Order BPPBJ DKI Jakarta - Ika Sech Syarini; Sihar Tambun (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
This research aims to determine the influence of accounting literacy and understanding of PP Number 55 of 2022 on MSME taxpayer compliance which is moderated by tax socialization. The research method used in this research is a survey method with a questionnaire and distributed to the research objects, namely MSME entrepreneurs registered on the DKI Jakarta BPPBJ E-order using Google Form with a sample of 100 respondents in this research. Data analysis in this research uses the SMART PLS version. 4.0. The results of the research show that accounting literacy has a positive effect on MSME taxpayer compliance, apart from that, tax socialization also influences MSME taxpayer compliance, but understanding PP Number 55 of 2022 has no influence on taxpayer compliance, and the moderating variable, namely tax socialization, has not been able to influences accounting literacy variables and understanding of Government Regulation Number 55 of 2022 on MSME taxpayer compliance.